Birr al-Walidain Konsep Relasi Orang Tua dan Anak dalam Islam - Nur I'anah (Faculty of Psychology Universitas Gadjah Mada, 2017)
In the family, a parent-child relationship deemed to be a complicated relationship. Parents as adult individuals who have the necessity to educate will tend to straighten up their children. And children are other individuals with different dimensions of life have a tendency to explore life by playing, hanging out, and learning. This relationship then often creates tension and misunderstanding as a result of ineffective communication and power relation in the status as a parent or a child. Islam offers the concept of birr al-validation for parent-child relations, which is ideal for maintaining the harmony of parent-child relationships and good for both. The article is aimed to discuss a virtue in the religion and society of Islam that governs the concept of parent-child relationship, namely birr al-validation. Virtue values contained in birr al-validation are needed to form a good relationship pattern between parent and child. The understanding of birr al-validation as a virtue that requires bidirectional relations will be able to benefit both parties (parents and children) and generate reciprocity and complementary so that parent-child relationship becomes intimate and have a positive impact for both psychological health.